Enabling participation in community-dwelling children and young people with acquired brain injuries and their families: a theory-based, evidence-based and person-based approach to intervention development - Jane Williams; Rachel Keetley; Emily Bennett; Joseph C Manning; Victoria Lyon; Jade Kettlewell; Kate Radford (BMJ Open)
Objective To codesign and develop an intervention to promote participation and well-being in children and young people (CYP) with acquired brain injury (ABI) and family caregivers.Design A complex intervention development study including a scoping review, mixed-methods study, co-design workshop and theoretical modelling.Setting Community-dwelling participants in one geographical region of the UK.Participants CYP with ABI (5–18 years) and their parents, health, education, social care and voluntary/third-sector practitioners.Results The intervention development process using a theory-driven and evidence-informed approach, combining the Behaviour Change Wheel and the person-based approach is described. Findings from the scoping review and mixed-methods study were analysed and synthesised using the framework method and the International Classification of Functioning, Health and Disability and the Behaviour Change Wheel. Evidence of identified participation needs, barriers and facilitators was presented at the codesign workshop. The findings demonstrate the significant long-term impact of an ABI on CYP participation and both CYP and parent well-being with significant unmet family needs. Barriers and facilitators were identified, with key barriers being lack of knowledge and understanding, lack of parental and family support and a need for cross-sector collaboration and communication. Stakeholders identified potential solutions and intervention ingredients, such as the need for education for families and schools regarding long-term impact of ABI, and longer-term practical and emotional support for families. Findings from the workshop were analysed using the framework method and synthesised with previous findings using the Behaviour Change Wheel. Theoretical modelling enabled guiding principles to be identified and an intervention logic model to be produced. ‘ABI-Participate’ is a novel, multifaceted intervention, developed with CYP with ABI, their parents and professionals from across health, education, social care and charity sectors. Using a case coordination model, ABI-Participate aims to address the unmet needs and barriers of this population and includes needs assessment, goal setting, action planning, health coaching, practical and emotional support for families and multiagency liaison and collaboration, adopting an individualised needs-based approach.Conclusion A systematic process using a theory-based, evidence-based and person-based approach resulted in a novel, codesigned, multifaceted intervention, grounded in an in-depth understanding of CYP with ABI participation needs, barriers and facilitators. Further development and refinement of the individual elements of ABI-Participate and the care pathway to support its implementation are now required prior to feasibility testing.